Clean and Healthy Living Behavior (PHBS) Strategy to Prevent the Spread of the Covid-19 Virus - Ana Fitia Rahmawati; Indah Kristantini (Proceeding of International Conference on Science, Health, And Technology, 2021)
The outbreak of the Corona Virus Diseases-19 or known as Covid19 has caused disasters for the community, resulting in the death of thousands of people around the world, including in Indonesia. The emergence of this disease outbreak encourages the importance of providing education to the public about clean and healthy living habits (PHBS). In addition, the public needs to know with certainty the transmission and ways of preventing Covid-19 so that it does not continue to become epidemic. People are strongly advised to stay at home only, have to wear masks, workers / employees work from home (WFH), always wash their hands and apply PHBS. PHBS is a strategy that can prevent the spread of Covod-19. The public continues to be urged to improve clean and healthy living habits in an effort to prevent the spread of Covid-19, because community behavior plays an important role in reducing the number of Covid-19 spread. PHBS is one of the strategies in preventing the spread of Covid -19 which is very effective and easy to do by all levels of society. The government's recommendations continue to urge the PHBS movement to be the key to preventing the spread of Covid 19 during this pandemic. Conducting PHBS, it is hoped that the spread of Covid-19 can be inhibited so that the incidence does not increase. Because of the importance of a clean and healthy lifestyle, it is necessary to provide continuous information so that it can increase the knowledge of all levels of society to apply PHBS in their daily life.